FAMILY BUSINESS SUCCESSION PLANNING ANALYSIS AT BENG GOAN GROUP - Gohat, Alvin; Honesta, Mellisa; Kristianto, Lewi Supranata (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The aim of this research is to review family business succession planning in the Beng Goan Group NTT that is currently in its 3rd generation to analyze and understand the steps that have been taken to build a sustained family business. The results obtained from this study the owner of the company has made a plan of succession, these stages consist of starting planning early, encouraging intergenerational teamwork, developing a written succession plan, involve the family and colleagues, taking advantage of outside help, establishing a training process, planning for retirement, and make retirement timely and unequivocal. In this research we use descriptive qualitative methods with semi structured interviews, the data validation process uses a triangulation test. The results show that succession planning has not been fully implemented in Beng Goan Group, future planning is to involve everyone and obtain outside help, develop a written succession plan, and make retirement timely and unequivocal so that the next generation can run the business with this step well.